Assessment tools used by elementary level adapted physical educators in Wisconsin - Steinbrunner, Pamela J. (My University, 1995)
School districts (N = 417) in Wisconsin were surveyed at the elementary level to determine what assessments tools were being used. A total of 131 surveys with responses were returned. These 131 surveys accounted for 175 districts and a 42% return rate. Of the 131 teachers responding 84% had the state of Wisconsin 860 add-on certification in Adapted Physical Education. Data were analyzed by grade level (early childhood, K-3 & 4-6). Results showed that the three most frequently used tools were Bruininks-Oseretsky Test of Motor Proficiency, Test of Gross Motor Development, and the Peabody Developmental Motor Scales. No single test was found to be used for any specific disability. Early childhood students were assessed most frequently with the Peabody Developmental Motor Scales for IEP objectives, programming services, or both. Kindergarten through 6th grade students were assessed with the Bruininks-Oseretsky Test of Motor Proficiency most often for IEP objectives, programming services, or both. There appeared to be a different variety of assessment tools used for early childhood than for the elementary students. However, at each level, three tools were predominantly used. Given the number of variables that should be attended to (e.g., age level, disability, and curriculum needs) there appeared to be a lack of well defined criteria used by districts to determine appropriate assessment tools for each student.
Keywords: Physical education for children with disabilities - Wisconsin